PENYUSUNAN LAPORAN KEUANGAN SESUAI STANDAR SAK EMKM PADA UMKM â€œNIKY COKLATâ€ KEDIRI (AKSIME : Jurnal Pengabdian Masyarakat Bidang Akuntansi, Manajemen & Ekonomi, 2024)
Abstract This research focuses on the application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) to the "Niky Coklat" MSME in Kediri City. This MSME, famous for its chocolate character, faces challenges related to recording financial reports that are simple and less organized. In its business procedures, from purchasing raw materials to marketing and selling products, research details every step. The mentoring method involves evaluating existing financial reports, introducing SAK-EMKM, improvement plans, and preparing guidelines and procedures according to standards. It is hoped that the results of this research will help "Niky Coklat" prepare financial reports that are accurate and meet standards. This not only improves internal business management but also supports the possibility of participation in external financing through investors or financial institutions. As a contribution to the implementation of SAK-EMKM among MSMEs, this research is expected to advance sustainable economic growth and improve the welfare of MSMEs and their contribution to the Indonesian economy. Keywords: Financial Reports, UMKM, SAK EMKM. Abstrak Penelitian ini fokus pada penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK-EMKM) pada UMKM "Niky Coklat" di Kota Kediri. UMKM ini, terkenal dengan coklat karakternya, menghadapi tantangan terkait pencatatan laporan keuangan yang sederhana dan kurang tertata. Dalam prosedur bisnisnya, dari pembelian bahan baku hingga pemasaran dan penjualan produk, penelitian merinci setiap langkah. Metode pendampingan melibatkan evaluasi laporan keuangan yang ada, pengenalan SAK-EMKM, rencana perbaikan, serta penyusunan pedoman dan prosedur sesuai standar. Diharapkan, hasil penelitian ini membantu "Niky Coklat" menyusun laporan keuangan yang akurat dan sesuai standar. Hal ini tidak hanya meningkatkan pengelolaan bisnis internal tetapi juga mendukung kemungkinan partisipasi dalam pembiayaan eksternal melalui investor atau lembaga keuangan. Sebagai kontribusi pada penerapan SAK-EMKM di kalangan UMKM, penelitian ini diharapkan dapat memajukan pertumbuhan ekonomi berkelanjutan dan meningkatkan kesejahteraan UMKM serta kontribusi mereka pada ekonomi Indonesia. Kata Kunci : Laporan Keuangan, UMKM, SAK EMKM.